Combination Foretinib and Anti-PD-1 Antibody Immunotherapy for Colorectal Carcinoma - Fu, Yuyin; Peng, Yujia; Zhao, Shengyan; Mou, Jun; Zeng, Lishi; Jiang, Xiaohua; Yang, Chengli; Huang, Cheng; Li, Yuyan; Lu, Yin; Wu, Mengdan; Yang, Yanfang; et al. (Frontiers in Cell and Developmental Biology, 2021)
Abstract Immune checkpoint inhibitors have achieved unprecedented success in cancer immunotherapy. However, the overall response rate to immune checkpoint inhibitor therapy for many cancers is only between 20 and 40%, and even less for colorectal cancer (CRC) patients. Thus, there is an urgent need to develop an efficient immunotherapeutic strategy for CRC. Here, we developed a novel CRC combination therapy consisting of a multiple receptor tyrosine kinase inhibitor (Foretinib) and anti-PD-1 antibody. The combination therapy significantly inhibited tumor growth in mice, led to improved tumor regression without relapse (83% for CT26 tumors and 50% for MC38 tumors) and prolonged overall survival. Mechanistically, Foretinib caused increased levels of PD-L1 via activating the JAK2-STAT1 pathway, which could improve the effectiveness of the immune checkpoint inhibitor. Moreover, the combination therapy remodeled the tumor microenvironment and enhanced anti-tumor immunity by further increasing the infiltration and improving the function of T cells, decreasing the percentage of tumor-associated macrophages(TAMs) and inhibiting their polarization towards the M2 phenotype. Furthermore, the combination therapy inhibited the metastasis of CT26-Luc tumors to the lung in BALB/c mouse by reducing proportions of regulatory T-cells, TAMs and M2 phenotype TAMs in their lungs. This study suggests that a novel combination therapy utilizing both Foretinib and anti-PD-1 antibody could be an effective combination strategy for CRC immunotherapy.